Are futures markets functioning well for agricultural perishables? Evidence from China's apple futures market - Qianqian Mao; Jens-Peter Loy; Thomas Glauben; Yanjun Ren (Agricultural Economics (Zemědělská ekonomika), 2023)
Emerging economies often establish commodity futures markets to discover price signals, manage price risks and improve market integration, but establishing a futures market may not be feasible for agricultural perishables. In this study, we evaluated the function of the world's first fresh fruit futures contract for apples. Combining partial cointegration with state-space modelling, we derived time-varying price discovery metrics for the apple futures market. Our findings revealed a limited and time-varying dominance of price discovery by the futures market, while a substantial share of price discovery occurred in the spot market. Moreover, poor convergence of disaggregated spot prices to the futures price suggests that commercial traders in the apple supply chain tended to focus more on the spot market than on the futures market. Thus, emerging economies should be cautious about the new establishment of futures markets for agricultural perishables. Future research using more specific data on the spot market may provide a better insight on the limited function of the futures market.
Keywords: 330; market integration; partial cointegration; price discovery; price transmission